Caracterización energética en sistemas de iluminación interior en el sector comercial para lograr una mayor eficiencia, un menor consumo y ahorro energético (2011)
Energy efficiency in terms of lighting is being considered an important item in production in many areas which this operate, or better, appropriate lighting is needed for daily and for extended time, therefore it has been greatly improved in this aspect, even in the aesthetic, not being the minor. New designs, more practical, and efficient invade the market in terms of brightness and fluorescence, which enable and provide the opportunity to implement projects or justified recommendations and evidence-based, measurements and conclusions. This paper characterizes and compares different types of lamps on the market in the area of interior lighting in the commercial sector, making modifications to a conventional lamp and a proprietary design of light that will be tested and measurements that will serve as a basis for comparative tables, analysis of data to be taken, and supportable conclusions for these tables. The idea is obtain greater efficiency in the system, therefore, pass an energy saving, including cost effective, on many occasions, not to mention that at all, is the purpose of any project or proposal in which required and can become more efficient.